Barbell strength training for non-specific low back pain rehabilitation: a prospective case series - Sandau, I.; Blau, S.; Witt, M. (sems-journal, 2021)
Abstract: Non-specific low back pain is considered a widespread disease and therefore leads to a high financial burden on the health care system. Among other things, reduced muscle strength of the trunk extensors is discussed as major risk factor. Therefore, the aim of the study was to examine the influence of a barbell training on the strength capacity of the trunk muscles and on the pain-related restrictions in the everyday life of low back pain patients. Nine patients (3 female, 6 male) carried out a barbell training for 8 weeks. Before and after the intervention, the isometric force of trunk flexion and trunk extension was measured. In addition, the determination of the pain-related restrictions in everyday life was assessed using a questionnaire. The barbell training led to a significant reduction in pain-related restrictions of everyday life (-12.5 %points, -63.7%). At the same time, the force-output for trunk extension (151.0 N, +30.7%) and trunk flexion (111.9 N, +25.9%) increased significantly. The correlation analysis showed that the decrease in pain-related restrictions of everyday life is highly correlated with the increased force-output of trunk extension. Furthermore, it became clear that a low flexion-extension ratio in the trunk seems typical in low back pain patients. In conclusion, it can be stated that a barbell training is suitable to the therapy of non-specific low back pain.